Fomento de valores, actitudes y normas de juego limpio en una academia de fútbol: la realidad a través del audiovisual. - Turizo Arzuza, Maritza
The present paper exposes the results of a research that allowed structuring a proposal of formation in values and attitudes directed to students of Basic and Media education, enrolled in a Soccer Academy. The project was based on the need to counteract the reluctance of teachers to try creative strategies based on technology and in particular, the incorporation of audiovisual to the processes of comprehensive training. A field design of descriptive scope was proposed, with a population sample of thirty young people between 13 and 15 years old. Through the application of two scale questionnaires of Likert, a disposition to good sports behaviors and appropriation of the ethical - axiological component was detected. However, it is necessary for the Sport Academy to consolidate values and attitudes for compliance with Fairplay rules. For this reason, a pedagogical proposal was drawn up based on the recreation and analysis of real cases of professional soccer players, expressed through audiovisual content. It is concluded that the implementation of the designed proposal, can help the learners to develop better behaviors inside and outside the classroom and the playgrounds.